1993
DOI: 10.1523/jneurosci.13-07-02853.1993
|View full text |Cite
|
Sign up to set email alerts
|

Immunological relationships of NGF, BDNF, and NT-3: recognition and functional inhibition by antibodies to NGF

Abstract: Polyclonal antibodies raised against mouse 2.5S NGF (mNGF) and against synthetic peptides made from hydrophilic portions of mNGF have been used to compare the immunological properties of mNGF, human recombinant brain-derived neurotrophic factor (hrBDNF), and human recombinant neurotrophin-3 (hrNT-3). Affinity-isolated antibodies raised against intact mNGF reacted with all three neurotrophins when tested by ELISA and totally or partially blocked the bioactivities of the proteins in survival assays of embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…ELISAs have shown that our polyclonal antibody recognizes NT-3, although to a significantly lesser extent than NGF and, to an even lesser extent, BDNF (Murphy et al, 1993), but in in vitro survival assays it blocks only the biological activity of NGF and not that of personal communication). In preliminary in vitro mouse dorsal root ganglia studies, our anti-NGF had a small effect on sprouting induced by NT-3, whereas BDNF-induced sprouting was unaffected ( Van der Zee et al, 1995).…”
Section: Preparation and Characterization Of Ngf And Its Antiserummentioning
confidence: 85%
“…ELISAs have shown that our polyclonal antibody recognizes NT-3, although to a significantly lesser extent than NGF and, to an even lesser extent, BDNF (Murphy et al, 1993), but in in vitro survival assays it blocks only the biological activity of NGF and not that of personal communication). In preliminary in vitro mouse dorsal root ganglia studies, our anti-NGF had a small effect on sprouting induced by NT-3, whereas BDNF-induced sprouting was unaffected ( Van der Zee et al, 1995).…”
Section: Preparation and Characterization Of Ngf And Its Antiserummentioning
confidence: 85%
“…Fortunately, our NGF antibody readily cross-reacts with NT3 [22] and immunoprecipitates both proNT3 and NT3. As shown in Fig.…”
Section: Processing Of Pront3mentioning
confidence: 99%
“…Our results indicate NGF-like immunoreactivity in mast cells of mesenchymal adult rodent tissues or RPMCs. Although some cross-reactivity of the polyclonal antibody toward other neurotrophins cannot be excluded (38) (7,8). Mast cells could, by releasing cytokines such as tumor necrosis factor, also indirectly upregulate NGF production in surrounding cells (35).…”
Section: Sympathetic (E10) and Drg (E8) Neurons Were Cultured 24mentioning
confidence: 99%